Results of the DIVA-1 Expedition of RV “Meteor” (Cruise M48:1):Three new species of Munnopsidae Sars, 1864 from abyssal depths of the AngolaBasin (Crustacea: Isopoda: Asellota) - Mursch, Andre; Brenke, Nils; Wägele, Johann Wolfgang (Zootaxa, 2008)
Three new species of Munnopsidae, Eurycope monodon sp. nov., E. denticollis sp. nov. and Munneurycope Persephone sp. nov. are described from the deep sea of the Angola Basin in the southeast Atlantic. E. monodon and E. denticollis closely resemble E. glabra Kensley, 1978 in general appearance and in the peculiar shape of the female operculum with an apex shifted far frontally, but with a less pronounced medial lobe of antenna 1 article 1, presence of dorsal tubercles on the pleotelson and uropods with less reduced exopods. Eurycope monodon has a rostrum bearing a single anteromedian spinelike seta and a male pleopod 1 with a subapical, hook-like cusp of the distolateral lobe curved anteriolaterally. Eurycope denticollis has paired and relatively shorter spine-like setae on the rostrum, and the cusp of pleopod 1 distolateral lobe is curved caudolaterally. M. persephone is the first species of the genus recorded from the South Atlantic. It differs from the most similar species, M. nodifrons (Hansen, 1916), in antenna 1 with elongated third article, a maxilliped with more distinctly truncate endite, and a different dentation on the retinacula.